Association of virginiamycin and multiple supplement for cattle fed a high-quality tropical forage - Vidal, Raphaela Cenci (2021)
The aim of this study was to evaluate the effect of adding virginiamycin to either mineral mixture or multiple supplement on intake, digestion, ruminal fermentation profile, rumen microbial production, blood metabolites, and liver metabolism of zebu heifers fed high- quality tropical forage. Eight heifers were used and assigned to a 4 × 4 Latin Square design. The treatments were: mineral mixture (MM), mineral mixture with virginiamycin (MM + V), multiple supplement (MSUP), and multiple supplement with virginiamycin (MSUP + V). The mineral mixture was provided daily at 120 g/ animal for the treatments MM and MM + V. The multiple supplement was formulated to provide 300 g of crude protein (CP)/ kg as fed and contained mineral mixture, corn grain, and urea: ammonium sulfate, and was daily provided at 200 g/animal. The amount of supplemental virginiamycin was based on a maximum theoretical response on animal performance (50 mg/100 kg body weight) and daily mixed to the supplements types. The treatments were compared according to a 2 × 2 factorial arrangement (mineral mixture and multiple supplement, with or without virginiamycin). All analyzes were performed using the MIXED procedure of SAS 9.4. Significant effects were declared at P<0.10. There was no interaction between virginiamycin and supplement type (P≥0.58) or effects of virginiamycin (P≥0.66) on voluntary intake. The multiple supplement decreased voluntary dry matter intake (P<0.07). The multiple supplement decreased digested organic matter (DOM) intake (P<0.10), but increased dietary CP:DOM ratio (P<0.01). There were no effects of virginiamycin (P≥0.44) or interaction between virginiamycin and supplement type (P≥0.61) on total digestibility or dietary DOM content. The multiple supplementation increased (P<0.08) the CP digestibility. The ruminal ammonia N concentration was only affected by supplement type (P<0.04). The molar proportions of individual volatile fatty acids were affected by the provision of multiple supplement (P<0.07), except for butyrate (P>0.76). There was an interaction between virginiamycin and supplement type on urine N excretion (P<0.08). The fecal-N excretion was decreased by multiple supplementation (P<0.06). Provision of virginiamycin decreased the blood hormone, IgF-1 (P<0.07), and the multiple supplementation increased blood urea-N (P<0.01). The geneexpression for propionyl-CoA carboxylase was affected by virginiamycin (P<0.01). An interaction between supplement type and virginiamycin was observed on the pyruvate carboxylase (P<0.01), and for citrate synthase gene expression (P<0.02). However, using a low-intake multiple supplement with high CP content for cattle fed high-quality forage causes a substitutive effect on forage intake, keeps the nitrogen retention unchanged. The virginiamycin supplementation seems to cause some post-prandial influences, which may vary according to the type of supplement. Therefore, this statement deserves further studies in order to obtain a clearer understanding. Keywords: Virginiamycin. Supplementation. N balance.